Evaluation of Water Quality of Lakhanvaram Lake : A Comparative Study of Three Locations of Lake - Neeta Kagada,; Prof. K. Shailaja, (International Journal of Scientific Research in Science and Technology, 2024)
The present study evaluated on the quality of Lakhanvaram Lake for two years during 202-23(April to March) and 2023-24(April to March) along with seasonal changes during the period of study. The research focuses on detecting, monitoring, and predicting water quality of lake at three different sites/locations using nineteen parameters viz., pH, Carbonates (CO3),Bicarbonates(HCO3), Chlorides (Cl), Dissolved Oxygen (DO), Biological Oxygen Dissolved (BOD), Organic Matter (OM), Chemical Oxygen Dissolved (COD), (TH), Calcium(Ca), Magnesium(Mg), Total Solids (TS), Total Dissolved Solids (TDS), Total Soluble Salts(TSS), Sulphur (SO4), Phosphorus(PO4), Nitrates (NO3) and Nitrites(NO2). The results demonstrated that Dissolved Oxygen (DO), Biological Oxygen Dissolved (BOD), Organic Matter (OM), Chemical Oxygen Dissolved (COD), (TH), Calcium(Ca), Magnesium(Mg), Total Solids (TS) and Total Dissolved Solids (TDS) increased during rainy season and pH, Dissolved Oxygen (DO), Biological Oxygen Dissolved (BOD) Chemical Oxygen Dissolved (COD) decreased during summer months in both the years of study. It indicated that the overall water quality will improve more if the period is sustained for another 2 to 3 years. The outcomes of the study will help the stakeholders develop effective regulations and strategies for the timely restoration of lake water quality.
Keywords: Water Quality Parameters; Lakhanvaram Lake Water; Physico-Chemical Properties; Biological Properties; Dissolved Oxygen; Biological Oxygen Dissolved; Chemical Oxygen Dissolved